PELAKSANAAN HAK DAN KEWAJIBAN PERDATA ORANG YANG TIDAK CAKAP HUKUM DI KABUPATEN SLEMAN - Imma Indra Dewi Windajani (Fakultas Hukum Universitas Gadjah Mada, 2008)
In principle every legal subject has legal competence, although not all legal subjects have capacity to act. Capacity to act is ability to do legal acts which have perfect legal consequences. In the districts of Sleman Regency there also persons who are categorized as unable to do legal acts, because they are not adult persons or having such conditions that they are unable to do legal acts which have perfect legal consequences by themselves. This research was focused on the implementation of civil rights and obligations of those who are legally unable in the district of Sleman Regency. The research result indicated that persons who are unable to do legal acts in the district of Sleman Regency carried out their rights and obligations dealing with administrative and economic problems through their guardians, although these guardians were not always appointed by the court decision but were only based on factors of blood relationship, psychological and sociological propinquities between those unable persons and their candidates of guardians.